Implementasi Islamisasi Ilmu Pengetahuan dan Pengilmuan Islam dan Penyusunan dan Pengilmuan Islam dalam Penyusunan Kurikulum Madrasah - Alim, Zul Fadhli Al (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The purpose of this study was to determine the implementation of the Islamization of Islamic knowledge and science and the formulation of Islamic knowledge in the preparation of the Madrasah Curriculum. To be able to reveal this, the authors use qualitative research methods using analysis techniques and data collection phenomena is carried out through literature studies or literature studies. The results of this study show that the Islamization of science basically refers to efforts to purify and construct knowledge from ideas that are contrary to Islam. Islamization is not just an activity of ayatization and labeling Islam as a science, but a process of promoting and developing an appropriate methodology based on Islamic concepts, so that the knowledge that emerges follows the building outlined by Islam that comes from God Almighty. Pro education of this nation. The idea of Islamization of Al Faruqi's knowledge is an effort that needs a positive response.